Echoes of “Ptahhotep” in the Greco-Roman Period? - Hagen, Fredrik (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
The article looks at continuity in the Egyptian literary tradition, in particular with regard to the rare phrase “partiality is the abomination of god” (bwt n t r rdít ḥr gs) found in “Ptahhotep” and later, as a marked quotation, in the “Installation of the Vizier”. It draws attention to the use of the same phrase as a divine epithet in Greco-Roman temple inscriptions, and argues that this may be an intertextual echo of “Ptahhotep”, although clearly it cannot be considered evidence for a late transmission of that text. Finally, it looks at the historical evidence for the association between Thoth and concept of ‘partiality’ (rdít ḥr gs, nm‘) .